Pelatihan Mendeley Reference Manager sebagai Media Optimalisasi Penguasaan Manajemen Referensi Format Ieee Style bagi Mahasiswa Baru - Wulandari Wulandari; Novelti Novelti; Darimis Darimis; Mumu Muzayyin Maq; Ediaman Sitepu (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to optimize new students' mastery of reference management using IEEE Style through training on the use of Mendeley Reference Manager. The activity involved three stages: preparation (identifying student needs and developing training modules), implementation (presentation of material, demonstration of Mendeley usage, and hands-on practice of IEEE Style reference management and citations), and evaluation (pre- and post-tests to measure understanding and participant response questionnaires). The results showed a significant improvement in new students' ability to manage references and apply IEEE Style, with an average post-test score 35% higher than the pre-test, and a participant satisfaction rate of 88% with the applicable and interactive training method. Therefore, Mendeley training is effective as a medium for optimizing new students' mastery of IEEE-standard reference management.